Slavia Centralis – ob 10. obletnici izhajanja - Ulčnik, Natalija (Slavia Centralis, 2020)
Natalija Ulčnik, technical editor of the magazine Slavia Centralis, which experienced its tenth anniversary in 2018, presents the topics of individual years of the magazine.
Keywords: Slavia Centralis; scientific journal; humanities; Slovenian literature; Slovene language; Slavic research